A REDUÇÃO DO TEMPO E DO ESPAÇO: A PROPÓSITO DO CONTO AS CORUJAS, DE MOREIRA CAMPOS - Sales de Souza, Francisco (Revista de Letras, 2016)
A REDUÇÃO DO TEMPO E DO ESPAÇO: A PROPÓSITO DO CONTO AS CORUJAS, DE MOREIRA CAMPOS